Notes from the Periphery: History and Methods. (2nd October 2019) - Vlachou, Foteini
Abstract : There is still no consensus on what (or when and where) the periphery is/has been. The centre–periphery opposition, criticised for its hierarchical and binary nature, has frequently been mapped onto the West–East divide, and scholars have questioned the applicability of the term from what it seems like a Eurocentric point of view. These notes reflect on the concept of periphery and its historiography, seeking to disentangle the periphery from its exclusive (and primarily geographical) association with the centre(s), using it instead to undercut the categories that have variously shaped and constrained the art historical discipline. It proposes the re-imagining of the study of the periphery as a fluid set of practices, with a strong association to fundamentally unequal power configurations, while assuming a wide range of methodological and theoretical positions.